RANCANG BANGUN ALAT PENETAS TELUR AYAM BERBASIS MIKROKONTROLER - M Taufiq Tamam; Arif Johar Taufiq; Gunawan P B (Techno (Jurnal Fakultas Teknik, Universitas Muhammadiyah Purwokerto), 2010)
Has done research on chicken egg incubator device based on microcontroller. This tool works by controlling the temperature in the hatching room, which is between 36 °C to 39 °C. Based on test results, the tool is able to hatch chicken eggs with a success rate to 60%. Key word: chicken egg incubator, microcontroller